2016
DOI: 10.3389/fpsyg.2016.00753
|View full text |Cite
|
Sign up to set email alerts
|

Examining Workplace Ostracism Experiences in Academia: Understanding How Differences in the Faculty Ranks Influence Inclusive Climates on Campus

Abstract: Research on the retention of women in academia has focused on challenges, including a “chilly climate,” devaluation, and incivility. The unique consequences of workplace ostracism – being ignored and excluded by others in an organizational setting – require focus on this experience as another interpersonal challenge for women in academia. The purpose of this study is to examine differences in the faculty experiences and outcomes of workplace ostracism, and to determine if these experiences are affected signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 42 publications
4
65
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Despite increasing female enrolment in medical school over the past 30 years, there has not been a proportional increase in the number of women in senior academic ranks. 7,[9][10][11] This is not only an issue related to equity or fairness. Increased female representation in senior academic ranks may increase an institution's overall productivity as demonstrated by studies examining the benefits of gender diversity in the workplace.…”
Section: Abstract Research Productivity Gender Psychiatry H-indexmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Despite increasing female enrolment in medical school over the past 30 years, there has not been a proportional increase in the number of women in senior academic ranks. 7,[9][10][11] This is not only an issue related to equity or fairness. Increased female representation in senior academic ranks may increase an institution's overall productivity as demonstrated by studies examining the benefits of gender diversity in the workplace.…”
Section: Abstract Research Productivity Gender Psychiatry H-indexmentioning
confidence: 99%
“…Figure 1a shows that 51.0% of respondents indicated that they were satisfied or very satisfied with their workplace culture, while a concerning 31.9% were somewhat or very dissatisfied with their workplace culture. Previous studies have identified diversity and inclusion as factors that have impact on senior academics’ dissatisfaction 15 , including the career progression for female academics 1618 . However, in our survey of Australian ECRs, most identified as satisfied, or at least unconcerned, regarding discrimination with respect to age, gender, ethnic background or sexual orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Population. In recent times, the HEIs have been recognized with 'chilly' and exclusionary climates (Bilal et al, 2019;Fatima et al, 2017;Zimmerman et al, 2016). Therefore, the current study emphasizes the higher education institutions operating in Pakistan and teachers are the unit of analysis to get responses about the outcomes of workplace ostracism.…”
Section: Samplementioning
confidence: 92%
“…The outcomes and responses of workplace ostracism vary across different contexts and situations (Williams, 2009) and qualitative exploration is much needed methodological approach for its in-depth inquiry (Waldeck, 2017). Yet the extant research studies are mostly quantitative (Fatima et al, 2017;Jahanzeb & Fatima, 2018;Zimmerman et al, 2016) that only offer limited insight into its consequences. Mao et al (2018) put forth the argument that behavioral outcomes of workplace ostracism are paradoxical and have mixed findings.…”
Section: Implications Limitations and Future Research Avenuesmentioning
confidence: 99%
See 1 more Smart Citation